Report generation tool / Yasser Mohamed Arifin - Yasser, Mohamed Arifin (2006)
This proposal, prepared for users who want to get a report like chart, save and print the report using online web based system without install any software. This tool can get data from user and process it to generate report or user can manage data by selected what data they need or categories data by group and choose type of chart. This tool an help user to develop report base on web application. User can select type of analysis and type of chart with 3D or 2D, colorful and animation type. User can choose to make analysis from data such as maximum or minimum, average, min data medium data,e and mode data.